Cross sectional study about intra-individual and inter-individual variability of subjective effort in submaximal sprint running in collegiate male sprinters - Tokutake, G.; Ueta, K. (Asian Journal of Sports Medicine, 2024)
Background:Although subjective exercise intensity is widely used to monitor training load in athletes, the reliability of subjective effort (SE) during high-intensity sprint running has not yet been established.